EFEKTIVITAS MODEL POE2WE TERHADAP HASIL BELAJAR SISWA PADA MATERI ALAT OPTIK - Sidik, Heri Maulana; Nurmahmuddin, Ariq (Universitas Negeri Makassar, 2020)
This study aims to determine student learning outcomes using the POE2WE (Prediction, Observation, Explanation, Elaboration, Write and Evaluation) model which is applied in the student learning process on optical instrument material. This research is an observational research and literature study. The observation research population was all SMA class XI students majoring in Mathematics and Natural Sciences. The objectives of this study were, 1) to determine how effective the POE2WE model is for learning physics in schools; and 2) to find out how effective the POE2WE model is on student learning outcomes in optical instrument material. The research sample consisted of 10 SMA class XI students majoring in Mathematics and Natural Sciences. The research instruments were questionnaires and knowledge tests conducted through online media such as Google Forms and Google Drive. The results of the data analysis explained that the application of the POE2WE model in learning physics on optical instrument material is: 1) Effectively applied in school learning; and 2) Effectively applied in learning physics on optical instrument material.Penelitian ini bertujuan untuk mengetahui hasil belajar siswa menggunakan model POE2WE (Prediction, Observation, Explanation, Elaboration, Write and Evaluation) yang diterapkan dalam proses pembelajaran siswa pada materi alat optik. Penelitian ini merupakan penelitian observasi dan studi pustaka. Populasi penelitian observasi adalah seluruh siswa SMA kelas XI jurusan MIPA. Tujuan dari penelitian ini adalah, 1) untuk mengetahui seberapa efektif model POE2WE terhadap pembelajaran fisika di sekolah; dan 2) untuk mengetahui sebarapa efektif model POE2WE terhadap hasil belajar siswa pada materi alat optik. Sampel penelitian terdiri dari 10 orang siswa SMA kelas XI jurusan MIPA. Instrumen penelitian berupa angket dan tes pengetahuan yang dilakukan melalui media online berupa Google Forms dan Google Drive. Hasil analisis data menjelaskan bahwa Penerapan model POE2WE dalam pembelajaran fisika pada materi alat optik adalah: 1) Efektif diterapkan dalam pembelajaran di sekolah; dan 2) Efektif diterapkan dalam pembelajaran fisika pada materi alat optik.